Photographs of the Warsaw Ghetto Uprising in Geoffrey Hill's The Triumph of Love. Issue 2 (3rd April 2022) - Phillips, Hannie
Abstract: Geoffrey Hill's approaches to memorializing the Holocaust in his poetry have been widely examined for his innovative, self-conscious, elegiac practice and their embodiment of the anxieties of the postmemorial witness. His 1998 book-length poem The Triumph of Love attempts to bear witness to the trauma of the Holocaust through numerous cross-cutting and argumentative sections which meditate on history, memory, and the role of the poet after atrocity. What is most striking about Hill's witnessing of the Holocaust in The Triumph of Love is his linguistic representations of photographs of the Warsaw Ghetto Uprising (1943), a complicated encounter between word and image which has not been previously examined. Hill selects photographs taken by Nazi photographers during the suppression of the Warsaw Ghetto Uprising in his poetic memorialization of the Holocaust. I argue that Hill depicts these photographs in order to refocus the narrative of perpetration embedded within the images. These reimagined photographs become linguistic objects capable of fostering a state memorialization within Hill's poem. I investigate The Triumph of Love by considering the role that perpetrator photographs can play in literary representations of post-Holocaust memory.